2011
DOI: 10.1177/0899764011419518
|View full text |Cite
|
Sign up to set email alerts
|

Why Urban Poor Donate

Abstract: This article presents the outcomes to a study of the charity donation behavior of 771 low-income people residing in three socially deprived Boroughs in inner-London. It emerged that several variables known to affect (a) levels of charity giving and (b) choices of types of charity supported among the U.K. public as a whole also influenced the donation behavior of the financially poor. In addition, it appeared that a participant’s sense of affinity with other low-income people and the degree to which the individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Similar trend has been observed in the UK (Bennett, 2012;Bashir et al, 2013), and Ireland (Donoghue and Ruddle, 2000;Carroll et al, 2005).…”
supporting
confidence: 73%
“…Similar trend has been observed in the UK (Bennett, 2012;Bashir et al, 2013), and Ireland (Donoghue and Ruddle, 2000;Carroll et al, 2005).…”
supporting
confidence: 73%
“…Our study investigated absolute rather than proportional giving, whereas most studies on the topic of how wealth influences giving use adult participants and focus on proportional giving, that is, what one gives relative to what one possesses (Bennett, 2012;James & Sharpe, 2007). We believe our approach is most suitable to answering the question of whether children expect to reap material benefits from a given social relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The associations reported above, however, are not universally observed (e.g., Andreoni, Brown, & Rischall, 2003;Bennett, 2012;Forbes & Zampelli, 1997;Helms & Thornton, 2012;Mesch, Osili, Ackerman, & Dale, 2015b;Piff, Kraus, Côté, Cheng, & Keltner, 2010;Piper & Schnepf, 2008). Inconsistencies in the associations between donor characteristics and giving suggest untested moderators, which I propose include characteristics of the beneficiary.…”
Section: Who Gives To Charity?mentioning
confidence: 79%
“…Generally, as expected, people with more money are seen to give more to charity (e.g., Choi & DiNitto, 2012;Hughes & Luksetich, 2008;Korndörfer et al, 2015). However, poorer donors give a greater share of their income (e.g., Bennett, 2012;Piff et al, 2010) and sometimes no relationship between income and giving is found (Neumayr & Handy, 2017;Shier & Handy, 2012). So, despite the obvious connection between having money and being able to share it with others, the relationship between income and charitable giving remains unclear.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation